LEISHMANIASIS: A REVIEW OF PATHOGENESIS, DIAGNOSIS, TREATMENT, AND CONTROL STRATEGIES (International journal of medical sciences, 2026)
Leishmaniasis is a tropical parasitic disease caused by Leishmania parasites and transmitted by sandflies. This disease can cause skin lesions, mucosal damage, or affect internal organs, depending on the type of infection. In this review, we summarize the current knowledge about leishmaniasis, including its causes, clinical forms, diagnosis methods, treatment strategies, and prevention measures. Special attention is given to the situation in Central Asia, especially Uzbekistan. Understanding these aspects is important for early detection, effective treatment, and control of the disease.